Biomechanical comparative analysis of conventional pedicle screws and cortical bone trajectory fixation in the lumbar spine: An in vitro and finite element study - Pei, Baoqing; Xu, Yangyang; Zhao, Yafei; Wu, Xueqing; Lu, Da; Wang, Haiyan; Wu, Shuqin (Frontiers in Bioengineering and Biotechnology, 2023)
Numerous screw fixation systems have evolved in clinical practice as a result of advances in screw insertion technology. Currently, pedicle screw (PS) fixation technology is recognized as the gold standard of posterior lumbar fusion, but it can also have some negative complications, such as screw loosening, pullout, and breakage. To address these concerns, cortical bone trajectory (CBT) has been proposed and gradually developed. However, it is still unclear whether cortical bone trajectory can achieve similar mechanical stability to pedicle screw and whether the combination of pedicle screw + cortical bone trajectory fixation can provide a suitable mechanical environment in the intervertebral space. The present study aimed to investigate the biomechanical responses of the lumbar spine with pedicle screw and cortical bone trajectory fixation. Accordingly, finite element analysis (FEA) and in vitro specimen biomechanical experiment (IVE) were performed to analyze the stiffness, range of motion (ROM), and stress distribution of the lumbar spine with various combinations of pedicle screw and cortical bone trajectory screws under single-segment and dual-segment fixation. The results show that dual-segment fixation and hybrid screw placement can provide greater stiffness, which is beneficial for maintaining the biomechanical stability of the spine. Meanwhile, each segment’s range of motion is reduced after fusion, and the loss of adjacent segments’ range of motion is more obvious with longer fusion segments, thereby leading to adjacent-segment disease (ASD). Long-segment internal fixation can equalize total spinal stresses. Additionally, cortical bone trajectory screws perform better in terms of the rotation resistance of fusion segments, while pedicle screw screws perform better in terms of flexion–extension resistance, as well as lateral bending. Moreover, the maximum screw stress of L4 cortical bone trajectory/L5 pedicle screw is the highest, followed by L45 cortical bone trajectory. This biomechanical analysis can accordingly provide inspiration for the choice of intervertebral fusion strategy.